Personalisasi Konten dan Pengaruhnya terhadap Minat Pelanggan Kota Medan di Marketplace Tiktok - Fitriana, Dhea; Sikumbang, Ahmad Thamrin (Universitas Syiah Kuala, 2025)
Customers on TikTok Marketplace, with a specific focus on the context of Medan City. The rapid development of digital technology has fundamentally transformed consumer behavior, where social media particularly TikTok has now become a primary platform for people to search for product information and make purchasing decisions. Through the use of advanced algorithms, TikTok is able to present content that is personally tailored to individual user preferences, thereby significantly increasing relevance and engagement. Content personalization has proven to offer a variety of strategic benefits in marketing, including enhanced brand awareness and equity, driving word-of-mouth marketing, increasing customer lifetime value, and optimizing the return on investment (ROI) of marketing campaigns. These benefits highlight the importance of personalization in building strong and sustainable customer relationships. Although personalization offers great potential to boost purchase intention and customer loyalty, this study also identifies potential challenges related to the